Determinan stabilitas perbankan di Indonesia: Pendekatan makro dan mikro prudensial - Dewi, Jayanti Sukma; Saraswati, Birgitta Dian (Universitas Hayam Wuruk Perbanas, 2023)
Banks have a very important role in the economy. Not only as financial intermediaries. They have also played a big role in the effectiveness of monetary policy. Therefore, bank stability is very important. This research aims to determine the influence of micro-prudential variables represented by CAR, NPL, and LDR variables, as well as the influence of macro-prudential variables represented by the Rupiah exchange rate variable against USD, inflation, interest rates, and IHSG, on bank stability in Indonesia, both in the short and long term. Using the vector error correction model (VECM) analysis technique, this research provides results that microprudential variables and macroprudential variables are both proven to have an influence on banking stability in Indonesia. Micro-prudential indicators such as CAR and LDR have been proven to have a positive effect on banking stability. Meanwhile, NPLs have a negative effect on banking stability. Likewise for macro-prudential indicators: the exchange rate and inflation have a negative effect on financial system stability. Meanwhile, interest rates and IHSG have a positive effect on banking stability. The impact of surprises or shocks that occur in micro-prudential and macro-prudential variables on banking stability is permanent. The implication of the findings in this research is that Bank Indonesia and the Financial Services Authority have a very large role in achieving banking stability in Indonesia.